The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1037/abn0000719
|View full text |Cite
|
Sign up to set email alerts
|

Context matters: Neighborhood disadvantage is associated with increased disordered eating and earlier activation of genetic influences in girls.

Abstract: Emerging evidence suggests socioeconomic disadvantage may increase risk for eating disorders (EDs). However, there are very few studies on the association between disadvantage and EDs, and all have focused on individual-level risk factors (e.g., family income). Neighborhood disadvantage (i.e., elevated poverty and reduced resources in one's neighborhood) is associated with increased risk for anxiety/depression and poor physical health. To date, no studies have examined phenotypic associations between neighborh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 71 publications
4
25
0
Order By: Relevance
“…By contrast, in girls, we found that gonadarche was critical for genetic effects, as there were substantially stronger genetic influences in midlate gonadarche (heritability ~50%) than preearly gonadarche (heritability ~0%; e.g. see Klump, 2013 for a review; Klump et al, 2017;Mikhail et al, 2021). In both sets of studies, developmental differences in genetic influences were not due to differences in age and once activated, the magnitude of genetic effects remained constant across later ages and developmental periods, suggesting that all of the genetic diathesis for eating disorder symptoms became activated during these pubertal stages.…”
Section: Example Findings In the Fieldmentioning
confidence: 76%
See 1 more Smart Citation
“…By contrast, in girls, we found that gonadarche was critical for genetic effects, as there were substantially stronger genetic influences in midlate gonadarche (heritability ~50%) than preearly gonadarche (heritability ~0%; e.g. see Klump, 2013 for a review; Klump et al, 2017;Mikhail et al, 2021). In both sets of studies, developmental differences in genetic influences were not due to differences in age and once activated, the magnitude of genetic effects remained constant across later ages and developmental periods, suggesting that all of the genetic diathesis for eating disorder symptoms became activated during these pubertal stages.…”
Section: Example Findings In the Fieldmentioning
confidence: 76%
“…(2022) studies in this issue show the profound impacts of minority stress and economic disadvantage, respectively, on youth psychopathology. Xu and Rahman (2022) described the potential importance of pubertal processes in heightening distress and psychological difficulties in lesbian, gay and bisexual (LGB) adolescents (see Discussion section of this article), and recent findings suggest that economic disadvantage significantly shifts the curve of genetic risk for eating disorder symptoms to much earlier in pubertal development in both boys and girls (Mikhail et al., 2021, in press). Examining minority stress and economic disadvantage alone, without considering pubertal development, would miss these critically important developmental processes and points of intervention for these at‐risk and often multiply disadvantaged populations.…”
Section: Gaps To Addressmentioning
confidence: 99%
“…Research findings from CIT methods may then guide future research studies that integrate traditional hypothesis testing methods to explore the associations between variables in a more intentional way to guide future preventive efforts. The results from this study highlight several variables that are already documented in the literature as pertinent risk factors for DEB, including appearance‐based teasing (Dahill et al, 2021), weight teasing (Eisenberg et al, 2012; Hunger et al, 2020; Puhl et al, 2014), everyday discrimination (Beccia et al, 2020; Yoon et al, 2022), gender (Keel et al, 2007; Maine & Bunnell, 2015; Pritchard et al, 2006), and financial difficulty (Richardson et al, 2015; Simone et al, 2021), as well as two variables collected during adolescence that have been explored less in the literature: receipt of public assistance and neighborhood safety (Mikhail et al, 2021) that are worth investigating further in future research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Physical environment represents another SDoH domain that may contribute to inequities in DEB risk. Recent research suggests that neighborhood disadvantage (e.g., low perceived safety) may increase DEB risk among girls (Mikhail et al, 2021). For instance, low neighborhood safety may restrict access to physical movement (e.g., running outside), which may in turn lead to the adoption of less healthy methods of weight control.…”
Section: Potential Social Determinants Of Health Contributing To Diso...mentioning
confidence: 99%
“…These results emphasize the importance of controlling for SES in order to reduce bias in estimates of genetic variance. A twin study revealed that neighborhood disadvantage was associated with increased disordered eating in girls across all stages of pubertal development, and the expected pubertal increases in genetic influences on disordered eating were only observed in girls from advantaged backgrounds [ 95 ]. Genetic influences on disordered eating were potentiated much earlier for girls living in disadvantaged contexts, suggesting interplay between genetic risk and SES.…”
Section: Introductionmentioning
confidence: 99%